Determinants of Voluntary Blood Donation: Motivations, Barriers, and Strategies for Enhancing Donor Recruitment and Retention in Madinah, Saudi Arabia - AlAhmadi, Riyad Ali; AlAhmadi, Bandar Ali M; Almuallim, Bader Mohammed; AlAhmadi, Hatem Musfer; Alhejaili, Adel Saleem; AlAhmadi, Bader Ali; Almutairi, Abdullah Barrak; Sanosi, Sultan Abdulhadi; Alzayed, Ahmed Abdullah; Almughamisi, Bassam; AlAhmadi, Ayman Mohammed; AlObedi, Abdurhman Saaaed; et al. (Journal of Posthumanism, 2024)
This study aimed to examine the key determinants of voluntary blood donation in Madinah, Saudi Arabia, focusing on identifying the major motivations and barriers and assessing their relationship with donor categories and socio-demographic characteristics.A sequential explanatory mixed-methods approach was employed. In the first phase, semi-structured interviews (n=25) were conducted to identify contextual themes, which subsequently informed the development of a structured survey administered in the second phase (n=50). The survey explored motivations, barriers, and demographic variables, and chi-square tests were performed to analyze associations with age, gender, education, and employment status.The findings indicated that altruism, religious and moral duty, and social responsibility were the most prominent motivations for blood donation. In contrast, fear of needles and pain, fear of weakness or dizziness, and lack of time emerged as the main barriers. Statistical analysis demonstrated significant associations between employment status and perceiving donation as a religious or moral duty (χ²=69.2, p<0.001), as well as between education level and perceiving it as a social responsibility (χ²=14.7, p=0.02 after collapsing categories). No significant associations were observed for age or gender.